Multiple breath washout analysis in infants: quality assessment and recommendations for improvement. (5th February 2016) - Anagnostopoulou, Pinelopi; Egger, Barbara; Lurà, Marco; Usemann, Jakob; Schmidt, Anne; Gorlanova, Olga; Korten, Insa; Roos, Markus; Frey, Urs; Latzin, Philipp
Abstract: Infant multiple breath washout (MBW) testing serves as a primary outcome in clinical studies. However, it is still unknown whether current software algorithms allow between-centre comparisons. In this study of healthy infants, we quantified MBW measurement errors and tried to improve data quality by simply changing software settings. We analyzed best quality MBW measurements performed with an ultrasonic flowmeter in 24 infants from two centres in Switzerland with the current software settings. To challenge the robustness of these settings, we also used alternative analysis approaches. Using the current analysis software, the coefficient of variation (CV) for functional residual capacity (FRC) differed significantly between centres (mean  ±  SD (%): 9.8  ±  5.6 and 5.8  ±  2.9, respectively, p   =  0.039). In addition, FRC values calculated during the washout differed between  −25 and  +30% from those of the washin of the same tracing. Results were mainly influenced by analysis settings and temperature recordings. Changing few algorithms resulted in significantly more robust analysis. Non-systematic inter-centre differences can be reduced by using correctly recorded environmental data and simple changes in the software algorithms. We provide implications that greatly improve infant MBW outcomes' quality and can be applied when multicentre trials are conducted.